INTEGRATING ISLAMIC VALUES IN CHARACTER EDUCATION TO PROMOTE INCLUSIVE HUMAN DEVELOPMENT: A CONCEPTUAL AND CONTEXTUAL ANALYSIS - Nurul Azizeh; Atika Rofiqatul Maula (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Contemporary education faces a crisis of character and a growing tendency toward exclusivity, which hinders the achievement of inclusive human development. This condition highlights the need for character education that is not merely normative but grounded in a holistic and contextual value framework. This article examines the integration of Islamic values—iman (faith), amal (action), and ihsan (ethical excellence)—as the foundation of character education oriented toward strengthening moral, social, and humanitarian dimensions. The study employs a conceptual and contextual analysis through a critical review of character education literature from both Western perspectives and Islamic educational thought. The findings indicate that iman functions as the basis of internal moral awareness, amal represents social practice and civic responsibility, while ihsan emphasizes ethics, empathy, and a humanitarian orientation in social relations. The integration of these three values contributes to a model of character education that is responsive to diversity and grounded in social justice. Therefore, the incorporation of iman, amal, and ihsan into curricula, learning processes, and educators’ role modeling is considered relevant in supporting inclusive human development in schools, madrasahs, and pesantren.